THE RELATIONSHIP OF CHILD ABUSE OF PARENTS WITH LOW SELF-ESTEEM CHILDREN AGED 8-12 YEARS - MUHAMMAD AL AZHARY; USWATUN HASANAH; LISA AGUSTIN (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
ABSTRACT Based on data from UNICEF (United for Children) in 2016 that 80% of children aged 2-14 years have experienced child abuse where 62% occurred in the family environment and school environment, the remaining 38% in public spaces. Child abuse as physical or mental violence, sexual violence and neglect of children under the age of 18 years. The purpose of this study was to determine the relationship between parental child abuse behavior and low self-esteem in children. Methods This research is a quantitative study that uses primary data and uses cross sectional research methods. The number of samples is 63 with total sampling technique. The results showed that high child abuse behavior with low self-esteem, namely 27 respondents 42.9%, high child abuse behavior with high self-esteem, namely 7 respondents 11.1%. Respondents with low child abuse behavior with low self-esteem amounted to 11 respondents 17.5%, low child abuse behavior with high self-esteem totaled 18 respondents 28.6%. The results of statistical tests using the chi-square test obtained p-value = 0.002 <ɑ = 0.05. The conclusion that there is a significant relationship between parental child abuse behavior with low self-esteem in children. Suggestions from the results of this study are expected to provide information about good child abuse behavior so that it is expected that child abuse behavior in children will decrease and self-esteem levels will increase. Keywords: child abuse, low self-esteem HUBUNGAN PERILAKU CHILD ABUSE ORANGTUA DENGAN HARGA DIRI RENDAH PADA ANAK USIA 8-12 TAHUN ABSTRAK Berdasarkan data UNICEF (United for Children) pada tahun 2016 bahwa 80% anak usia 2-14 tahun pernah mengalami child abuse dimana 62% terjadi dilingkungan keluarga dan lingkungan sekolah, selebihnya 38% diruang publik. Child abuse sebagai kekerasan fisik atau mental, kekerasan seksual dan penelantaran terhadap anak dibawah usia 18 tahun. Tujuan Penelitian ini adalah untuk mengetahui hubungan perilaku child abuse orangtua dengan harga diri rendah pada anak. Metode Penelitian ini merupakan penelitian kuantitatif yang mengunakan data primer dan memakai metode penelitian cross sectional. Jumlah sampel sebanyak 63 dengan Teknik total sampling. Hasil Penelitian menunjukan bahwa perilaku child abuse tinggi dengan harga diri rendah yaitu 27 responden 42,9%, perilaku child abuse tinggi dengan harga diri tinggi yaitu 7 responden 11,1%. Responden dengan perilaku child abuse rendah dengan harga diri rendah berjumlah 11 responden 17,5%, perilaku child abuse rendah dengan harga diri tinggi berjumlah 18 responden 28,6%. Hasil uji statistic dengan menggunakan uji chi-square diperoleh nilai p-value=0,002<ɑ=0,05. Kesimpulan bahwa ada hubungan yang signifikan antara perilaku child abuse orangtua dengan harga diri rendah pada anak. Saran dari hasil penelitian ini diharapkan dapat memberikan informasi tentang perilaku child abuse yang baik sehingga diharapkan perilaku child abuse pada anak akan menurun dan tingkat harga diri akan meningkat. Kata Kunci: Harga diri rendah, Kekerasan pada anak